Avaliando diferentes estratégias na Ucrânia e seus efeitos nos sistemas internacionais - Etesami, Soheil (2024)
The recent war between Russia and Ukraine, which is considered as the biggest and most important military conflict in Europe after the Second World War, will leave deep consequences on the relations of countries in addition to the pervasive effects on the level of the international system. A crisis in one region affects the interests of other actors in other regions; therefore, the disruption of the balance of power in the relations between the great powers following Russia's attack on Ukraine includes opportunities and threats for international actors. Based on this, the current article aimed to answer the question, “What impact will Russia-Ukraine conflict have on the international system?”. The research hypothesis was proposed in such a way that the recent crisis in Ukraine can affect the international system in economic, security, and social axes. The findings of the research showed that the war in Ukraine would probably have had global effects on the food, energy and economic systems. The analysis method used in this research was descriptive and analytical, and to achieve the main goal of the research, which was to investigate the possible effects of the war between Russia and Ukraine on the international system and global actors, the theoretical framework of offensive realism was used.